Sposobnost prepoznavanja težav in okrevanje - Rotar, Eli (Rehabilitacija (Ljubljana), 2016)
Methods: Twenty patients after TBI participated in the study. We measured their quality of performance of activities of daily living tasks with the AMPS. Based on the A3 questionnaire, the patients described where they had noticed problems. By comparing the two sets of results we inferred the level of their awareness of their own limitations. Results: The TBI patients with a low score on process skills have more difficulties in recognising their limitations. In this group, large discrepancies between the therapist's and the patient's assessment of the patient's performance were observed. Conclusion: The patients are not always aware of their limitations. A3 proved to be a useful therapeutic tool in occupational therapy intervention. The obtained information was important for choosing, planning and implementing appropriate intervention strategies to improve the patient's quality of life.
Keywords: Assessment of Awareness of Ability; brain damage; Brain Injuries; delovna terapija; možganske poškodbe; Occupational Therapy; ocena zavedanja sposobnosti; samozavedanje; self-awareness